Longitudinal Volume Assessment of Reconstructed Breast Using Three-Dimensional Measurement: How Do DIEP and LD Flap Change Immediately after Surgery? - Hiroki Utsunomiya; Ryutaro Tanaka; Shuryo Akamine; Taro Kusano; Tomoaki Kuroki; Koichi Kadomatsu (Indian Journal of Plastic Surgery)
Background The deep inferior epigastric perforator (DIEP) and latissimus dorsi (LD) flaps are two widely used autologous breast reconstructions. Despite studies on flap-volume changes, the time of the first measurement is not immediately after surgery. Therefore, this study aimed to investigate the change in volume over time from the immediate postoperative period using a three-dimensional (3D) scanner.